Air convection embankment experimental feature design phase 1 - Goering, Douglas J.
Prior research work has indicated that air convection embankments are a promising technique for limiting the thaw settlement damage that often occurs when roadway embankments are constructed in regions of warm permafrost. These studies lead to the proposal of a full-scale experimental air convection embankment (ACE) to be constructed through the Federal Experimental Features in Construction Program. A work plan for including an ACE in the Parks/Chena Ridge interchange project (Federal Project No. I-0A4-5(7), State of Alaska Project No. 63538) was forwarded and approved in 1994. This project report discusses the design and construction of the Parks/Chena Ridge ACE experimental feature which occurred during 1996 and 1997.